Regional poster exhibition - Floethe, Richard, artist (NYC : WPA Federal Art Project, 1936)
Poster for Federal Art Project exhibition of posters from New York and New Jersey at the Federal Art Gallery, 225 West 57th Street, New York City, showing abstract design.